EVALUASI FUNGSI REGULASI PADA SEKTOR KESEHATAN DI KABUPATEN SUMBAWA - Rusmayadi Rusmayadi (LPPM STIKES Griya Husada Sumbawa, 2017)
One of the municipal government obligations that are strategic is to make regulation in the licensing and certification of personnel of hospitals and health center. Unfortunately, the municipal government of Sumbawa, West Nusa District Health Department data for 2010 shows none of the hospital or Puskesmas had the licenses. From the previous study, we can’t find any documentation about licensing and certification of personnel. It is thus necessary to evaluate the function of municipal government in regulates the health area. To evaluate the regulatory function of municipal government in health area in Sumbawa seen from the input, process and output. This research is a qualitative descriptive study, which describe a situation or phenomenon in a comprehensive manner in the context of the actual. The design of this research is normative, the evaluation of the licensing and certification regulatory functions in the health sector in the district of Sumbawa compared with the standart in the implementation of licensing and certification regulations. The result prove that the functions of municipal government as the regulator has not run optimally, it is seen from the limited availability of inputs such as regulation of health care institution, human resources, instruments, and systems. The implementation (process) is more focused on the regulating the private facilities without any training of controlling, as the result, none of the Hospital and health center have license and no one has been certified (output). The implementation of regulations on municipal of Sumbawa has not specifically regulated in local legislation, so implementation process is not going well, give impact to the government-owned health care providers who haven’t any licenses for establishing and operating the hospital, and health professionals haven’t ant certification.